Female Buddha at Ukubahāḥ of Lalitpur resemble with Alchi Sum-tsek Monastery, Ladakh - Bajracharya, Birat Raj (Historical Journal, 2024)
In Buddhism, enlightenment is accessible to all, regardless of gender. In the highest teachings of Tantra, a unique aspect emerges: the existence of five female transcendental Buddha-s, known as the prajña of Pañca Buddha. Alternatively, they are sometimes interpreted as the Pañca Buddha themselves in female form. One such set of goddesses has been discovered in Ukubahāḥ, a vihāra in the old city of Patan, Nepal. This article focuses on researching these previously underappreciated sculptures from Ukubahāḥ. It highlights striking similarities between the iconography of 9th century’s Ukubahāḥ sculptures and 11th to 13th century murals at Alchi Monastery in Ladakh. Among the five Tārā-s, three identical depictions are identified in Alchi’s Sum-tsek Monastery. For this study, a comparative analysis was conducted solely on the depictions from Ukubahāḥ in Nepal and the Sum-tsek monastery in Ladakh. The Female Buddha at Ukubahāḥ in Lalitpur resembles those at Alchi Sum-tsek Monastery, Ladakh.